Pupil Cycle Time Distinguishes Migraineurs From Subjects Without Headache - Cortez, Melissa M.; Rae, Natalie; Millsap, Leah; McKean, Nick; Brennan, K. C. (Frontiers in Neurology, 2019)
Migraine is a neurological disorder characterized by paroxysms of head pain accompanied by trigeminovascular system activation and autonomic dysfunction. Diagnosis is currently based on clinical diagnostic criteria. Though physiological differences exist between migraineurs and non-headache controls, true physiological biomarkers have been elusive, especially for the full clinical spectrum of migraine, inclusive of chronic, episodic, and probable migraine. We used edge-light pupil cycle time (PCT) as a probe of the pupillary light circuit in migraine, paired with clinical assessment of migraine characteristics, and compared these to non-headache controls. We found significantly increased PCT in probable, episodic, and chronic migraine, compared to controls. Additionally, increased PCT correlated with the presence of craniofacial autonomic symptoms, linking pupillary circuit dysfunction to peripheral trigeminal sensitization. The sensitivity of PCT, especially for all severities of disease, distinguishes it from other physiological phenotypes, which may make it useful as a potential biomarker.